(untitled) - Blaustein, Dan (New York, 1999)
This book includes 3 units and 18 chapters: Unit 1: Life science: What is life?, Cells, Heredity and reproduction, Diversity and adaptations,...; Unit 2: Physical science: What is matter?, Properties and changes, Forces and motion,...; Unit 3: Earth science: The solar system and beyond, Earth materials, Earth's structure, Water,...
Keywords: Khoa học đời sống,Science,Earth sciences,Life sciences,Physical sciences; Học và giảng dạy (Bậc Trung học),Study and teaching ( Secondary ),Study and teaching ( Secondary ),Study and teaching ( Secondary ),Study and teaching ( Secondary )